Biblical faith an evolutionary approach - Theissen, Gerd; Bowden, John (Philadelphia, PA Fortress, 1984)
Includes bibliographical references and index.
Originally published : Biblishe Glaube in evolutionarer Sicht.--Christian Kaiser Verlag, Munich, 1984.
Keywords: Biblical theology